FAKTOR YANG MEMPENGARUHI DISIPLIN KERJA DENGAN FINGERPRINT SEBAGAI PEMODERASI PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA PROVINSI KALBAR - Angga Yoga; Muhammad Zalviwan (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2023)
The current technological developments are no longer in doubt, even today technology has become a necessity in the sector of human life. Fingerprint is the only attendance tool that can meet data needs using only fingerprint verification. According to Hasibuan (2006194-198) good discipline reflects the magnitude of a person's sense of responsibility for the tasks assigned to him. In conducting research, an analytical method is needed related to the problems in this study. This study uses quantitative analysis with two variables using fingerprint and work discipline. According to Sugiyono (2012: 92) the results of data analysis were collected through distributing questionnaires formed through a measuring scale. Based on the research, it shows that the objective and ability variables significantly influence work discipline: It is known that the tcount value of the objective and ability variable is -2.205 while the ttable value is 2.02439. This means tcount -2.205 ttable 2.02439, so it can be concluded that the objective and ability variables significantly influence work discipline. In the X validity test (factors of work discipline) it is declared valid because it is seen from the r count r table (0.263), the validity test (fingerprint/moderation system) is declared valid because it is seen from the r count r table (0.263), and the Y variable test ( work discipline) is declared valid because it can be seen from the r count r table (0.263).